Targeting DNGR‐1 (CLEC9A) with antibody/MUC1 peptide conjugates as a vaccine for carcinomas. Issue 7 (17th April 2014) - Picco, Gianfranco; Beatson, Richard; Taylor‐Papadimitriou, Joyce; Burchell, Joy M.
<x xml:space="preserve">Abstract</x> DCs are the most potent APCs and are the focus of many immunotherapeutic approaches for the treatment of cancer, although most of these approaches require the ex vivo generation and pulsing of DCs. We have targeted a subset of DCs in vivo using an Ab to DNGR‐1, a C‐type lectin dedicated to the cross‐presentation of Ag expressed by subsets of DCs. HLA‐A2 epitopes from the tumour‐associated Ag, MUC1, were coupled to the anti‐DNGR‐1 Ab, and their efficacy in generating a Th1‐cell response and inhibiting tumour growth was evaluated in a clinically relevant double transgenic mouse model expressing human MUC1 and A2K/b. Using this strategy, we demonstrate that an effective immune response to MUC1 can be generated, which results in a significant delay in the growth of MUC1‐expressing tumours in both prophylactic and therapeutic settings. In addition, we also show, using PBMCs isolated from healthy volunteer blood, that target an MUC1 HLA‐A2 epitope to human DNGR‐1 in vitro can induce an MUC1‐specific CD8+‐T‐cell response, which confirms the relevance of our in vivo murine results in the human setting.